Meta-Analysis the Effect of a Potassium Nitrate Desensitizing Agent and Casein Phosphopeptide Amorphous Calcium Phosphate on Tooth Sensitivity after Office Bleaching Treatment - Safitri, Diyanti; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Office bleaching is a treatment used to treat tooth discoloration, but it often results in tooth sensitivity. The desensitizing agent potassium nitrate and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) can reduce tooth sensitivity because they work to inhibit nerve transmission, thereby preventing the sensation of pain. This study aimed to investigate the effect of potassium nitrate desensitization agents and CPP-ACP on tooth sensitivity after bleaching treatment.Subjects and Method: This was a meta-analysis with the following PICO format. Population= Patients who have undergone office bleaching treatment. Intervention= desensitizing agents potas-sium nitrate and CPP-ACP. Comparison: without desensitizing agent. Outcome: tooth sensitivity. Keywords used